2021
DOI: 10.1002/ajoc.202100482
|View full text |Cite
|
Sign up to set email alerts
|

Practical Syntheses and Luminescent Properties of Arene‐substituted Arsines

Abstract: Aryldiphenylarsines, diarylphenylarsines, and triarylarsines were synthesized by practical methods to utilize the heavy atom effect for phosphorescence. 1‐Naphthyl, 2‐naphthyl, 9‐phenanthryl, and 1‐pyrenyl groups were introduced in the present work. The obtained arene‐substituted arsines showed phosphorescence in solutions at 77 K. On the other hand, 1‐pyrenyl‐substituted arsines showed only fluorescence in the solid states at 77 K, whereas the others exhibited phosphorescence. In addition, oxidation of the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Hexafluoroacetylacetone (hfa) was purchased from Tokyo Kasei, Inc. (Tokyo, Japan). Triphenylarsine oxide ( 1 ), 15 triphenylphosphine oxide ( 2 ), 16 9-phenyl-9-arsafluorene oxide ( 3 ), 7 tri(1-naphthyl)arsine oxide ( 4 ), 17 Eu(hfa) 3 (H 2 O) 2 , 4 Gd(hfa) 3 (H 2 O) 2 , 4 Eu 3+ -complex of 2 ( 2-a ), 11 and Gd 3+ -complex of 2 ( 2-b ) 18 were synthesized according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Hexafluoroacetylacetone (hfa) was purchased from Tokyo Kasei, Inc. (Tokyo, Japan). Triphenylarsine oxide ( 1 ), 15 triphenylphosphine oxide ( 2 ), 16 9-phenyl-9-arsafluorene oxide ( 3 ), 7 tri(1-naphthyl)arsine oxide ( 4 ), 17 Eu(hfa) 3 (H 2 O) 2 , 4 Gd(hfa) 3 (H 2 O) 2 , 4 Eu 3+ -complex of 2 ( 2-a ), 11 and Gd 3+ -complex of 2 ( 2-b ) 18 were synthesized according to literature procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Naka and co-workers synthesized 12 arene-substituted arsines, starting from nonvolatile arsenic precursors such as iododiphenylarsine (Ph 2 AsI), diiodophenyl arsine (PhAsI 2 ), and tribromoarsine (AsBr 3 ), to study the effect of As on photoluminescence properties. [89] The nonvolatile arsenic precursors were treated with the corresponding aryllithium reagents (ArLi) to give the products in moderate to good yields (Scheme 11). The presence of different arene groups on the As center does not affect the longest absorption maxima (λ abs ) of 57-60 in UV-Vis absorption.…”
Section: Arene-substituted Arsinesmentioning
confidence: 99%
“…We have developed practical As–C bond formation reactions to synthesize various organoarsenic compounds . While creating the arsine library through our synthesis methods, we reported that the effect of the electronic structure multiplied by the heavy atom effect of arsenic modulates the ISC and phosphorescence process. , Annulated organoarsenic compounds exhibited diverse emission properties caused by modulation of the excited singlet (S n , n = 1, 2, 3...) and T n states, as well as the heavy atom effect of arsenic. , …”
Section: Introductionmentioning
confidence: 99%